Pengaruh Parameter Milliampere-Second (mAs) terhadap Kualitas Citra Dan Dosis Radiasi Pada Pemeriksaan CT scan Kepala Pediatrik - Muhammad Irsal; Guntur Winarno (Jurnal Fisika FLUX, 2020)
Radiographers are responsible for administering radiation doses according to the principle of As Low As Reasonably Achievable (ALARA), to optimize the use of CT parameters to produce good image quality by minimizing radiation doses. The purpose of this study was to determine the effect of mAs parameters on image quality and radiation dose received by pediatric CT head examination patients. The research method to perform image processing results of examination using radiant viewer and analysis of value Contrast to noise ratio (CNR) as a parameter of image quality and CTDIvol to determine the estimated radiation dose, then an analysis is performed to determine whether there is an influence of mAs on the CNR and CTDIvol values. The mean value of kV 116 ± 8.28, the mean value of parameter mAs 161.5 ± 63.46, the mean SNR parameter value is 7.5 ± 0.8, the mean return value of CNR parameter was 0.318 ± 0.291, the mean value of the CTDIvol parameter is 18.68 mGy ± 4.55 mGy, the average value of DLP parameters was 408.7 mGy x cm ± 105.2 mGy x cm, the mean value of parameter DLP is 441.2 mGy x cm ± 155.2 mGy x cm. With linear regression analysis of test results between mAs to CNR is R2 = 0.045. then to the results of linear regression between mAs against CTDI is R2 = 0704, the estimated radiation dose limit for the average value of CTDIvol 18.68 mGy and the average value of DLP 408.7 mGy x cm, this means the protocol CT scan of the head of the pediatric use is still within safe limits by Diagnostic Reference Level of BAPETEN in 2018 to pediatric head CT examination